Adakitic magmas: modern analogues of Archaean granitoids - Martin, Hervé (Lithos, 1999)
Both geochemical and experimental petrological research indicate that Archaean continental crust was generated by partial melting of an Archaean tholeiite transformed into a garnet-bearing amphibolite or eclogite. The geodynamic context of tholeiite melting is the subject of controversy. It is assumed to be either (1) subduction (melting of a hot subducting slab), or (2) hot spot (melting of underplated basalts). These hypotheses are considered in the light of modern adakite genesis. Adakites are intermediate to felsic volcanic rocks, andesitic to rhyolitic in composition (basaltic members are lacking). They have trondhjemitic affinities (high-Na 2O contents and K 2O/Na 2O∼0.5) and their Mg no. (0.5), Ni (20–40 ppm) and Cr (30–50 ppm) contents are higher than in typical calc-alkaline magmas. Sr contents are high (>300 ppm, until 2000 ppm) and REE show strongly fractionated patterns with very low heavy REE (HREE) contents (Yb≤1.8 ppm, Y≤18 ppm). Consequently, high Sr/Y and La/Yb ratios are typical and discriminating features of adakitic magmas, indicative of melting of a mafic source where garnet and/or hornblende are residual phases. Adakitic magmas are only found in subduction zone environments, exclusively where the subduction and/or the subducted slab are young (<20 Ma). This situation is well-exemplified in Southern Chile where the Chile ridge is subducted and where the adakitic character of the lavas correlates well with the young age of the subducting oceanic lithosphere. In typical subduction zones, the subducted lithosphere is older than 20 Ma, it is cool and the geothermal gradient along the Benioff plane is low such that the oceanic crust dehydrates before it reaches the solidus temperature of hydrated tholeiite. Consequently, the basaltic slab cannot melt. The released large ion lithophile element (LILE)-rich fluids rise up into the mantle wedge, inducing both its metasomatism and partial melting. Afterwards, the residue is made up of olivine+clinopyroxene+orthopyroxene, such that the partial melts are HREE-rich (low La/Yb and Sr/Y). Contrarily, when a young (<20 Ma) and hot oceanic lithosphere is subducted, the geothermal gradient along the Benioff plane is high, so the temperature of hydrated tholeiite solidus is reached before dehydration occurs. Under these conditions, garnet and/or hornblende are the main residual phases giving rise to HREE-depleted magmas (high La/Yb). The lack of residual plagioclase accounts for the Sr enrichment (high Sr/Y) of the magma. Experimental petrologic data show that the liquids produced by melting of tholeiite in subduction-like P– T conditions are adakitic in composition. However, natural adakites systematically have higher Mg no., Ni and Cr contents, which are interpreted as reflecting interactions between the ascending adakitic magma generated in the subducted slab and the overlying mantle wedge. This interpretation has been recently corroborated by studies on ultramafic enclaves in Batan lavas where olivine crystals contain glass inclusions with adakitic compositions [Schiano, P., Clochiatti, R., Shimizu, N., Maury, R., Jochum, K.P., Hofmann, A.W., 1995. Hydrous, silica-rich melts in the sub-arc mantle and their relationships with erupted arc lavas. Nature 377 595–600.]. This is interpreted as demonstrating that adakitic magmas passed through the mantle wedge and interacted with it. Sajona [Sajona, F.G., 1995. Fusion de la croûte océanique en contexte de subduction collision: géochimie, géochronologie et pétrologie du magmatisme plioquaternaire de Mindanao (Philippines). Unpublished thesis, Brest University, France, 223 pp.] also considers that the high-Nb basalts, which are associated with adakites, reflect mantle–adakite interactions. Recent structural studies have demonstrated that plate tectonics operated during the first half of Earth history. The very strong similarities that exist between modern adakites and Archaean tonalite, trondhjemite and granodiorite (TTG) attest that both have the same source and petrogenesis. Consequently, when Archaean-like P– T conditions are exceptionally realised in modern subduction zones, Archaean-like magmas are generated. Contrarily, hot spots never produce TTG-like magmas, thus, strongly supporting the hypothesis of the generation of the Archaean continental crust within a subduction environment. However, Archaean TTG are poorer in Mg, Ni and Cr than adakites, indicating that mantle–magma interactions were less efficient, probably due to the shallower depth of slab melting. In this case, the slab-derived magmas rise through a thinner mantle wedge, thus, reducing the efficiency of the interactions. This is corroborated by the absence of a positive Sr anomaly in TTG, which indicates that plagioclase could have been a residual phase during their genesis.